A study of parking problems in Muar town. Case study: street on Muar town (Jalan Salleh) / Abdul Azim Abdul Malek - Abdul Malek, Abdul Azim (Faculty of Architecture, Planning and Surveying, 2012)
Parking facility can be considered as part of planning requirement that can affect development scheme as a whole. The increases of population, paralel with the increasing of road users lead to parking concerns, especialy in Muar Johor. Insuffiecient car park and congested traffic occured in that area, and the study keen to conduct a research to identify the factors that contribute to the problem. The scope of parking problem is narrowed to Jalan Salleh as the main road in Muar town. The author will investigate the parking management system at Muar town from planning, organising and controlling point of view. The demand for property in Muar is increasing, but with problems of lack of parking space and congested area can change property buyers decision. There are several factors that contribute to parking problem in Muar area, and public behavior and the poor management at Majlis Perbandaran Muar are two major concerns that the study will focus on. Based on structured interviews, survey and observation, it is hope that this study can come out with a good solution to help fix the situation before it become worst in the future.